2023
DOI: 10.5812/msnj-138254
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sleep Hygiene Education on Sleep Quality, Depression, and Fatigue of Hemodialysis Patients

Faezeh Ebrahimi,
Saeed Sokhtseraei,
Ali Navidian

Abstract: Background: One of the conservative treatment methods for patients with end-stage renal failure is hemodialysis. Although hemodialysis contributes to patients’ lives, it has adverse emotional and psychological effects, including sleep problems, fatigue, and depression. Objectives: The present study aimed to examine the effect of sleep hygiene education on sleep quality, depression, and fatigue among hemodialysis patients admitted to hospitals affiliated with Zahedan University of Medical Sciences in 2021. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…One of the most fundamental human needs and a critical component of health is sleep, according to Maslow's hierarchy of needs. Worldwide, 50-80% of dialysis patients have trouble sleeping (7) . Maintaining good health and leading an active life, both physically and intellectually, depend on getting enough sleep.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most fundamental human needs and a critical component of health is sleep, according to Maslow's hierarchy of needs. Worldwide, 50-80% of dialysis patients have trouble sleeping (7) . Maintaining good health and leading an active life, both physically and intellectually, depend on getting enough sleep.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that improving the sleep quality can reduce levels of fatigue in geriatric patients who experience difficulty falling asleep. This suggests that hemodialysis patients' sleep problems could be effectively treated in order to improve their overall health and wellness (7) . (11,12) .…”
Section: Introductionmentioning
confidence: 99%